INTEGRATION OF ISLAMIC VALUES IN ENGLISH LEARNING AT MADRASAH IBTIDAIYAH TEACHER TRAINING PROGRAM (PGMI) UIN NORTH SUMATERA - Riris Nur Kholidah Rambe; Salminawati Salminawati (JURNAL TARBIYAH, 2019)
This study aimed to find out: (1) HowEnglish Language Teaching Materials were; (2) How  the Concept of Islamic Values in English Language Teaching Materials was; and (3) How to integrate Islamic values in English teaching materials at the Madrasah Ibtidaiyah Teacher Training program (PGMI) at UIN North Sumatra. This research was library research which is one type of qualitative research. The fundamental characteristic in this study was that the data studied was written literature in the form of documents namely books or literature. This study analyzed the English material taught in PGMI Study Program, then integrated with Islamic values on some material in English courses. The research findings were 1) English teaching materials which were used in PGMI discussed five basic abilities, namely reading, vocabulary, writing, grammar, and speaking; 2) the concept of Islamic values which wasintegrated into English learning was contained in an integrated syllabus;3) in integrating Islamic values in English language lectures, there were several aspects that needed to be combined, including approach, curriculum, teaching material, and lecture methods.